The role of partial splenic artery embolization in the management of refractory esophageal variceal bleeding due to portal vein thrombosis - Büşra Tetik Dinçer; Nafiye Urgancı; Aylin Hasanefendioğlu Bayrak; Özlem Durmaz; İlgin Özden (BMC Pediatrics)
Abstract Background Gastro-esophageal variceal hemorrhage (GEVH) is one of the major causes of life-threatening gastrointestinal bleeding in children. Medical, endoscopic, angiographic, and surgical interventions can be utilized in treatment. In this case report, we describe partial splenic artery embolization for refractory GEVH due to portal vein thrombosis. Case presentation A 3-year-old male patient was admitted with abdominal distension. He had been followed up for hepatosplenomegaly for 2 years. The patient's body weight was 15.5 kg (50-75th percentile, 0.69 SDS) and height was 96 cm (50-75th percentile, 0.27 SDS). The general condition was moderate, and the skin appeared pale. The liver was palpable 2 cm, and the spleen was palpable 6 cm below the costal margin. Other system examinations were normal. Laboratory findings included hemoglobin (Hgb) of 7.1 g/dL, hematocrit (Hct) of 24%, white blood cell count of 9800/mm3, platelets of 67000/mm3, and INR of 1.3. Abdominal CT angiography demonstrated a hypodense thrombus at the portal confluence, almost completely occluding the lumen. Endoscopy revealed esophageal varices at the 2 and 7 o'clock positions in the distal esophagus, which became more prominent with insufflation and had red spots on them. Hyperemia was observed in the corpus and antrum of the stomach. Findings were consistent with stage 3 esophageal varices and increased vascularity in the duodenum due to portal vein thrombosis. Medical treatment with a proton pump inhibitor and beta-blocker was initiated. The patient underwent endoscopic band ligation (EBL) three times over 9 months. Despite EBL, the patient presented with GEVH three times during a 1.5-year follow-up. Due to newly developed multiple varices observed on control endoscopy a decision was made to perform splenic artery embolization. Interventional radiology performed selective lower splenic pole embolization. Six months later, the patient underwent another selective embolization. The patient has been followed up for 3 years without GEVH. Conclusions In this case, splenic artery embolization was observed to be an effective, repeatable, and safe treatment method for patients with hypersplenism caused by portal hypertension and refractory esophageal variceal bleeding.